Klaim Superlatif dan Penyesatan dalam Iklan Lux dan Shopee terhadap Tinjauan Etika - Nadia Safira Putri; Cut Amelia Hasymi; Salsabila Andiasari Banowati; Erwan Sudiwijaya (Universitas Muhammadiyah Klaten, 2026)
Advertising plays a crucial role in marketing by conveying information about goods and services to consumers. It has evolved beyond mere promotion to influence consumer perceptions and behaviors, especially in the context of globalization and technological advances. However, ethical challenges have emerged, including misleading information and the exploitation of vulnerable groups, which can result in negative social impacts. This research employs a qualitative descriptive approach to analyze potential breaches of the Indonesian Advertising Ethics Code as observed in the Lux Hijab Series and Shopeepay Later advertisements. Key violations included the use of superlative language, misleading claims about product ingredients, and religious exploitation for marketing purposes. The study highlights the importance of adhering to ethical advertising practices and the legal obligations tied to transparency and accountability in marketing communications. Findings suggest the need for careful consideration of ethical standards in advertising to avoid consumer deception, thereby contributing valuable insight into the significance of ethical adherence in promotional activities.